A 19-year-old girl with sharp, severe, and stabbing pain for 2 days (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
This article has no abstract. The first 100 words appear below:A 19-year-old female presented with severe, sharp, and stabbing pain on her lower left posterior segment for 2 days. The pain was poorly localized and it transferred to the head and ear region. The pain was stimulated by the application of heat. The patient also complained about a significant rise in the intensity of the pain on lying posture. She also complained about having tooth sensitivity on other segments of the arch. On clinical examination, the lower-left 2nd molar tooth was found to be broken down.